Effects of customary drugs and modified herbal therapy on blood glucose and total antioxidant capacity in Streptozotocin induced diabetes in albino rats: A comparative analysis - Siddiqui, Iftikhar Ahmed; Hassan, Syed Hafeezul; Ahmed, Faisal; Sarwar, Muhammad; Iqbal, Kefi (International Journal of Pharmacology and Toxicology, 2013)
346 million people worldwide have diabetes. In 2004, an estimated 3.4 million people died from consequences of high blood sugar. Diabetes and its complications have a significant economic impact on individuals, families, health systems and countries. Diabetes increases the risk of heart disease and stroke. Some evidences suggest that oxidative stress may play an important role in the etiology of diabetes and diabetic complications. The free radicals can be encountered by the treatment of diabetes mellitus with insulin and/or oral synthetic hypoglycemics. These are giving encouraging results, yet they are expensive, painful giving undesirable psychological effects. Alternatively, some plants and trace elements may be proven the candidates to bring about the promising and desirable results including Coriander and Vanadyl sulphate. To produce hypoglycemic effects a huge amount of Coriander (200 mg/kg/day/15days) and Vanadyl sulphate (0.75mg/100gm/day/17days) is required. This quantity is expensive and toxic. Even small dose (0.3 and 0.5 mmol/kg) of vanadyl sulphate may cause toxicity but during our study, the dose used of vanadyl sulphate and Coriandrum sativum, to evaluate the insulinomimetic activity, did not exhibit any lethal effect. In the present study, an innovate method has been developed in which the vanadyl sulphate was up taken by coriander that being in its natural environment probably through auto-oxidation rendered it non toxic. Pharmacological studies of vanadyl sulphate uptaken herb demonstrated no deleterious effects.